2003
DOI: 10.1002/anie.200390037
|View full text |Cite
|
Sign up to set email alerts
|

The Catalytic Intermolecular Orthoarylation of Phenols

Abstract: The use of Wilkinson's catalyst with diisopropylphosphinite ligands acting as cocatalysts allows the catalytic orthoarylation of phenols [Eq. (1)], a process that relies on a CH activation of a phenol that has been incorporated into the cocatalyst by transesterification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(95 citation statements)
references
References 20 publications
1
89
0
5
Order By: Relevance
“…4 The importance of such processes is also connected with an apparent significance of catalytic C-H bond functionalization in chemical synthesis. 5 Indeed, this quest has been the driving force behind enormous efforts in the synthetic community including our group, 6 culminating in a wealth of useful catalytic systems employing Pd, 7 Rh, 8 Ru, 9 and Ir 10 for the C-H bond arylation of heteroarenes with aryl electrophiles. 11…”
mentioning
confidence: 99%
“…4 The importance of such processes is also connected with an apparent significance of catalytic C-H bond functionalization in chemical synthesis. 5 Indeed, this quest has been the driving force behind enormous efforts in the synthetic community including our group, 6 culminating in a wealth of useful catalytic systems employing Pd, 7 Rh, 8 Ru, 9 and Ir 10 for the C-H bond arylation of heteroarenes with aryl electrophiles. 11…”
mentioning
confidence: 99%
“…The important feature of this methodology is the remarkably mild reaction conditions and excellent functional group tolerance. [73][74][75][76][77] In a recent report the application of a strong paccepting ligand P[(OCH(CF 3 ) 2 ) 3 ] proved viable for the rhodium-catalyzed direct arylations of unactivated arene 46 under microwave irradiations. 78,79 The absence of coordinating moiety resulted in a mixture of ortho-48 and para-substituted 49 regioisomers (Scheme 10), which suggested that an electrophilic aromatic substitution type-mechanism was operative.…”
Section: Electrophilic Aromatic Substitution (S E Ar Mechanism)mentioning
confidence: 99%
“…(51). [103] The significant point of this reaction is the use of phosphinite as a co-catalyst. The phosphorus atom coordinates to the rhodium atom, then electrophilic substitution with the rhodium(III) species occurs at the ortho position.…”
Section: Catalytic Arylation Of C à H Bondsmentioning
confidence: 99%